Międzynarodowa współpraca publikacyjna patrologów na przykładzie analizy korespondencji ks. profesora Wincentego Myszora z Archiwum Archidiecezjalnego w Katowicach - Gołda, Agnieszka; Tałuć, Katarzyna (Vox Patrum, 2022)
The paper presents the circumstances of international cooperation of Fr. Prof. Wincenty Myszor (1941-2017). Fr. W. Myszor was a lecturer at the Warsaw Academy of Catholic Theology and the Faculty of Theology at the University of Silesia in Katowice. The research of a historical, biographical and bibliographical character was conducted mainly through content analysis and document research. The analysed documents come from 6 fonds of the legacy bearing reference numbers from 169/1 to 169/6 and spanning 1970-2008, keptat the Archdiocesan Archives in Katowice. The contentanalysis describes: the circumstances of printing Myszor's texts in „Enchoria. Zeitschrift für Demotistik und Koptologie” and „Jahrbuchs für Antike und Christentum”; Myszor’s relations with editorial offices „Aufstieg und Niedergang der römischen Welt. Geschichte und Kultur Roms im Spiegel der neueren Forschung”, „Reallexikon für Antike und Christentum. Sachwörterbuch zur Auseinandersetzung des Christentums mit der antiken Welt”, The Coptic Encyclopaedia, Lexikons für Theologie und Kirche and editors of magazines („Bibliotheca Orientalis”, „Chronique d’Egypte”, „Orientalia”). In the second part of the text, Myszor's contacts are characterized with: „Bibliographia Patristica. Internationale patristische Bibliographie”, the bibliographic department in „Enchoria. Zeitschrift für Demotistik und Koptologie”, David M. Scholer – the author of Nag Hammadi Bibliography. The reconstructed fate of international interactions is part of the current of research devoted to the history of contacts between Polish researchers and scientists from the West, initiated in the period of of the Polish People's Republic.